The association between impulsivity and alcohol/drug use among prison inmates. - Bernstein, Michael H; McSheffrey, Savannah N; Van Den Berg, Jacob J; Vela, Jamie E; Stein, L A R; Roberts, Mary B; Martin, Rosemarie A; Clarke, Jennifer G (Addictive behaviors, 2015)
Few studies have examined the relation between impulsivity and drug involvement with prison inmates, in spite of their heavy drug use. Among this small body of work, most studies look at clinically relevant drug dependence, rather than drug use specifically.
Keywords: Adult; Aged; Alcoholism; Cognitive Therapy; Female; Humans; Impulsive Behavior; Male; Middle Aged; Prisoners; Smoking Cessation; Substance-Related Disorders; Young Adult